2007
DOI: 10.1261/rna.509007
|View full text |Cite
|
Sign up to set email alerts
|

Dynactin suppresses the retrograde movement of apically localized mRNA in Drosophila blastoderm embryos

Abstract: Motor dependent transport of mRNA is a key mechanism in axis specification during development. Apical transport and anchoring of wingless and pair-rule transcripts in the Drosophila syncytial blastoderm embryo is mediated by cytoplasmic Dynein, the major minus end directed microtubule dependent molecular motor. Here, we show that, despite apical transport of mRNA being highly directional, mRNA particles often pause and move backward toward the plus ends of microtubules. We suggest that this retrograde movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…We found that all movement of bcd *GFP particles is completely eliminated in Dhc mutant oocytes, including both unidirectional and bidirectional motility (Movie S6). These observations are consistent with recent evidence that Dynein can mediate both minus- and plus-end directed transport [911]. The minimal amount of bcd detected at the anterior cortex could be due to residual Dynein function of the hypomorphic alleles used, which is sufficient at least to permit oogenesis (Figure 2D–2F).…”
Section: Resultssupporting
confidence: 91%
“…We found that all movement of bcd *GFP particles is completely eliminated in Dhc mutant oocytes, including both unidirectional and bidirectional motility (Movie S6). These observations are consistent with recent evidence that Dynein can mediate both minus- and plus-end directed transport [911]. The minimal amount of bcd detected at the anterior cortex could be due to residual Dynein function of the hypomorphic alleles used, which is sufficient at least to permit oogenesis (Figure 2D–2F).…”
Section: Resultssupporting
confidence: 91%
“…When published, the functional significance of the interaction was unknown, but our data supports the hypothesis that it may be important. Our recent work[24]establishes that plus-end droplet motion is driven by kinesin-1, so it is unlikely that the effects of BicD on plus-end motion are simply due to its effects on dynein, although recent work suggests that this may be the case for some mRNA transport[25]. Second, the large phase IIb run length peak is absent in the t = 3 null, consistent with the hypothesis that BicD can acutely up-regulate both directions of transport.…”
Section: Discussionsupporting
confidence: 77%
“…The mechanism of localization of MS2x6 RNA by this fusion protein was reminiscent of that exhibited by endogenous apical transcripts in wild-type embryos, being sensitive to preinjection of functionblocking antibodies to dynein subunits (Fig. 1B) (Wilkie and Davis 2001) and driven by rapid bidirectional movements with an overall bias in the minus-end direction (Supplemental Movie 1; Bullock et al 2006;Vendra et al 2007). Thus, in flies, as in mammals (Hoogenraad et al 2003), the role of the BicD CTD in dynein transport can be functionally substituted by a heterologous recognition motif.…”
Section: A Conserved Role Of the Ctd Of Drosophila Bicd In Recruitingmentioning
confidence: 93%